2023
DOI: 10.3390/biomedicines11102777
|View full text |Cite
|
Sign up to set email alerts
|

Clonal and Scalable Endothelial Progenitor Cell Lines from Human Pluripotent Stem Cells

Jieun Lee,
Hal Sternberg,
Paola A. Bignone
et al.

Abstract: Human pluripotent stem cells (hPSCs) can be used as a renewable source of endothelial cells for treating cardiovascular disease and other ischemic conditions. Here, we present the derivation and characterization of a panel of distinct clonal embryonic endothelial progenitor cells (eEPCs) lines that were differentiated from human embryonic stem cells (hESCs). The hESC line, ESI-017, was first partially differentiated to produce candidate cultures from which eEPCs were cloned. Endothelial cell identity was asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…Recognizing that cellular source impacts the contents of exosomes raises the possibility that exosomes from other cell sources maybe more therapeutic for the treatment of stroke than those included in this review. For example, we have found that hESC derived endothelial progenitors produce more potent angiogenic exosomes than adult MSCs [90]. Additionally, while most studies included in this review used MSCs, there was variability in both the organism and the tissue from which MSCs were isolated, including rats [58,64], mini-pigs [66], and humans [21,66], and from either bone marrow [19,20,58] or adipose tissue [66].…”
Section: Source Of Exosomes In Stroke Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Recognizing that cellular source impacts the contents of exosomes raises the possibility that exosomes from other cell sources maybe more therapeutic for the treatment of stroke than those included in this review. For example, we have found that hESC derived endothelial progenitors produce more potent angiogenic exosomes than adult MSCs [90]. Additionally, while most studies included in this review used MSCs, there was variability in both the organism and the tissue from which MSCs were isolated, including rats [58,64], mini-pigs [66], and humans [21,66], and from either bone marrow [19,20,58] or adipose tissue [66].…”
Section: Source Of Exosomes In Stroke Therapymentioning
confidence: 99%
“…Therefore, the source of exosomes with well-defined identity and homogeneity, stability, and scalability, all of which allow for optimal production and high potency, will be advantageous for usage of exosomes in future clinical applications. One potential solution to is the use of clonally pure hESC derived progenitor cells as a scalable source of exosomes [90,96]. It is critical to provide cell sources for large scale production and manufacturing process developed in Good Manufacturing Practices (cGMP) conditions, which includes in-process testing, quality control release procedures, the standard operating procedure (SOP) for production, and the development of product release criteria for the final exosome product.…”
Section: Clinical Trials and A Perspective On Potential Future Direct...mentioning
confidence: 99%
“…Recognizing that cellular source impacts the contents of exosomes raises the possibility that exosomes from other cell sources may be more therapeutic for the treatment of stroke than those included in this review. For example, we have found that hESC-derived endothelial progenitors produce more potent angiogenic exosomes than adult MSCs [ 94 ]. Additionally, while most studies included in this review used MSCs, there was variability in both the organism and the tissue from which MSCs were isolated, including rats [ 61 , 69 ], mini-pigs [ 62 ], and humans [ 21 , 62 ], and from either bone marrow [ 19 , 20 , 61 ] or adipose tissue [ 62 ].…”
Section: Exosome Application In Stroke Therapymentioning
confidence: 99%
“…Therefore, the source of exosomes with well-defined identity and homogeneity, stability, and scalability, all of which allow for optimal production and high potency, will be advantageous for usage of exosomes in future clinical applications. One potential solution is the use of clonally pure hESC-derived progenitor cells as a scalable source of exosomes [ 94 , 102 ]. It is critical to provide cell sources for large-scale production and a manufacturing process developed in Good Manufacturing Practices (cGMP) conditions, which includes in-process testing, quality control release procedures, the standard operating procedure (SOP) for production, and the development of product release criteria for the final exosome product.…”
Section: Clinical Trials and A Perspective On Potential Future Direct...mentioning
confidence: 99%